Badan Penyelenggara Jaminan Sosial (BPJS) Sebagai Syarat Peralihan Hak Atas Tanah - Faradila Attamimi; Merry Tjoanda; Novyta Uktolseja (PATTIMURA Law Study Review, 2023)
ABSTRACT: The inclusion of BPJS provisions as stated in Presidential Decree No. 1 of 2022 as a condition for transferring land rights in the community has drawn some controversy and criticism, because this has nothing to do with buying and selling land and BPJS for health. The government should increase the transparency of BPJS health management and services if it wants to attract people to become participants. This legal research focuses on normative juridical research with a conceptual approach and statutory approach, the analytical method used is descriptive qualitative. The legal materials in this study are primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials are then interpreted and analyzed. The results of the study show that the Presidential Instruction (Inpres) Number 1 of 2022 is in principle the same as Government Regulation Number 24 of 1997, except that Presidential Instruction Number 1 of 2022 includes the addition of the requirement for a Photocopy of BPJS Kesehatan Participant Card for the purpose of registering the transfer of land rights. This research also shows that there is no relationship (correlation) between the inclusion of the BPJS requirements and the registration of the transfer of land rights because it is considered insignificant or has no relationship at all with the interest in transferring names in terms of transferring land rights, but it is related to the government's commitment to ensure that all levels of society have health insurance, namely optimizing the implementation of the National Health Insurance program.